Comparative study of the age of receiving therapeutic services in clients referred to Isfahan Cleft Care Team - Fatemeh Derakhshandeh; Hedieh Hashemi; Mehrdad Meemarzadeh (Vesnu Publications, 2011)
Background: Due to numerous difficulties of patients suffering from various types of cleft lip and/or palate, their therapeutic management involves an interdisciplinary teamwork. The aim of present study was to compare the mean age of receiving teamwork intervention including speech therapy, secondary surgery, alveolar bone grafting and orthodontics among early-referred and late-referred patients visited at Isfahan Cleft Palate Team. Materials & Methods: In this study, we first reviewed 260 charts of patients with cleft lip and palate and then, based on their age at the time of entrance to cleft care team, divided them into two groups the early references and late references. These two groups were compared on four variables: the mean age of beginning speech therapy, the mean age of palate secondary surgery, alveolar bone grafting and the average age of receiving orthodontics. All data of interest were statistically analyzed through t test. Results: The main results of the present study are as follows: (1) For 134 patients, who were referred to speech therapy, the mean age of initiating speech therapy in early- and late-referred clients was 3.3 and 9 years respectively. (2) For 47 patients, who underwent secondary surgery, the mean age of conducting early surgery was 3.88 years compared to late-referred group who had had this kind of intervention at 15.7 years of age on average. (3) 9 and 16.69 years were the respective mean age of early and late referral to alveolar bone grafting in 17 patients who had received this intervention and (4) for 24 patients who had received orthodontic services, the mean age of early-referred clients was 7.66 years compared to 17.05 years which was the mean age of referral in second group. Conclusions: The results suggest that there is a significant difference between early and late referrals with regard to the mean age of receiving secondary surgery, alveolar bone grafting, speech therapy and orthodontic services. Key words: Cleft palate, Secondary surgery, Speech therapy, Early intervention